2020
DOI: 10.1002/cche.10256
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and morphological changes in corn grains and starch during the malting for Palomero and Puma varieties

Abstract: Background and objective Although corn is the most consumed and studied cereal in Mexico as food, its potential in fermented beverage production is less considered. The objective was to study the morphological and physiochemical changes during malting for Palomero and Puma corns, and to compare them with malted barley to determine the potentials of this cereal in the beer industry. Findings The SEM images of the malted starches showed a selective enzymatic attack and germination rate and reducing sugars behave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 31 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…The relative crystallinity was detected in the following order: KMB > HHB > HPB, with HPB exhibiting a significantly (P < 0.05) low level of 18.5% (Table 2 ). In line with previous studies (Hernández-Becerra et al, 2020 ), no change in A-type crystal structures was observed in this study; however, a peak of weak intensity was observed at 17° 2θ and 18° 2θ for HPM, and the relative crystallinity was reduced across all cultivars after malting (Table 2 ). This suggests that certain crystalline regions may experience a slight decrease due to the activity of starch hydrolase during malting.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The relative crystallinity was detected in the following order: KMB > HHB > HPB, with HPB exhibiting a significantly (P < 0.05) low level of 18.5% (Table 2 ). In line with previous studies (Hernández-Becerra et al, 2020 ), no change in A-type crystal structures was observed in this study; however, a peak of weak intensity was observed at 17° 2θ and 18° 2θ for HPM, and the relative crystallinity was reduced across all cultivars after malting (Table 2 ). This suggests that certain crystalline regions may experience a slight decrease due to the activity of starch hydrolase during malting.…”
Section: Resultssupporting
confidence: 93%
“…A recent study using corn in malting observed fine holes in the starch particles in the regions of hydrolase attack and no change of A-type starch crystal structures as the enzymatic activity was selective during malting. The results indicated that an enzymatic attack had occurred in the amorphous region of the starch particles (Hernández-Becerra et al, 2020 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…La nula afectación de la superficie del granulo, se debe a que la modificación no involucró ningún tipo de tratamiento enzimático. La base Ca (OH)2 y el ácido CH3COOH, no degradan la superficie del granulo, contrario a lo que sucede con las enzimas bacterianas [24], o en procesos fermentativos o fisiológicos [25], con enzimas propias del proceso de germinación de semillas. Se pueden observar algunas formas sobre las micropartículas, que no se podrían clasificar como alteraciones del granulo, sino más bien, algunas estructuras adheridas al granulo, que pueden ser proteínas, o polisacáridos no amiláceos, relacionados con la dificultad que presentó la harina para su purificación.…”
Section: Morfología De Las Micropartículasunclassified
“…Malts from wheat, sorghum and finger millet have been tested for their malting efficiency and as adjuncts in brewing [13]. Sorghum and maize are usually used adjuvants in Europe as alternatives for malt [14,15,16]. Malted maize and sorghum along with the barley malt are in use in the production of some brands of beer [17].…”
Section: Introductionmentioning
confidence: 99%